(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The history of Uzbekistan is ancient and intertwined with significant global civilizations, considered one of the cradles of world civilization. The history of Uzbekistan reflects the life experiences of our ancient and recent ancestors, shedding light on their way of life and contributions to the progress of world history. In general, the study of the history of Uzbekistan involves analyzing historical events that occurred in the lives of our ancestors, understanding the reasons and significance of these events, considering internal and external factors, and exploring general and unique patterns.